Policies for Overcoming the Impact of El Nino on the Agricultural Sector in Sinjai Regency - Sumardi, Sumardi; Haris, Abd (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The agricultural sector of Sinjai Regency shows significant vulnerability to climate change, especially the El Nino phenomenon. It was recorded that hundreds of hectares of agricultural land were damaged. The main objective of this research is to comprehensively identify and analyze the impact of El Niño on agricultural land damage in Sinjai Regency. In addition, this research aims to formulate policy recommendations and concrete actions that can be taken by the government and other stakeholders to reduce the negative impact of El Niño. This research uses a qualitative approach. Data was collected through interviews, documentation and field observations. The use of NVivo 12 Plus analysis tools is also maximized. These findings confirm that El Niño has caused significant damage to agricultural land in Sinjai Regency, with 13 hectares experiencing puso or total crop failure, as well as 244 hectares of light damage, 137 hectares of moderate damage, and 50 hectares of heavy damage. This damage has a direct impact on agricultural productivity and food security, threatening farmer incomes and local food supplies. To deal with this impact, the government has implemented adaptive policies such as mapping affected locations, providing clean water, distributing food aid, and supporting farmer groups. Going forward, the government needs to strengthen weather monitoring systems, develop water management infrastructure, improve training for farmers, and strengthen partnerships between various parties to reduce the impact of El Niño and repair land damage.